Artificial Intelligence (AI) in Tourism Entrepreneurship: A Systematic Literature Review - Nofia Ulan Sari; Asmar Yulastri; Yuliana Yuliana; Yudha Aditya Fiandra (Lembaga Pengembangan Kinerja Dosen, 2026)
Artificial Intelligence (AI) has become one of the key technologies driving digital transformation in various sectors, including tourism entrepreneurship. Although research on AI continues to grow, studies that specifically map its development, applications, benefits, and challenges in tourism entrepreneurship remain relatively limited. Therefore, this study aims to systematically review the literature on AI in tourism entrepreneurship using a Systematic Literature Review (SLR) approach combined with bibliometric analysis. Research data were obtained from the Scopus database, covering the period 2020–2026. The article selection process follows PRISMA 2020 guidelines, and bibliometric analysis is conducted using VOSviewer to map publication trends, author collaboration networks, and relationships among keywords. The results show that publications on AI in entrepreneurship have increased significantly in recent years, with contributions from developed countries and journals focusing on innovation, sustainability, and entrepreneurship. Keyword analysis identified that the most studied AI applications include machine learning, natural language processing, chatbots, and generative AI such as ChatGPT. In addition, AI has been proven to deliver benefits such as increased operational efficiency, data-driven decision-making, service personalization, and business model innovation. However, its implementation still faces challenges, including limited digital competencies, high investment costs, and data security and privacy issues. This research provides a comprehensive understanding of the development and direction of AI research in tourism entrepreneurship and offers a research agenda to support the digital transformation of the tourism sector in the future.